Meningkatkan Motivasi Belajar Siswa Menggunakan Metode Pembelajaran Kooperatif Tipe Jigsaw Pada Siswa Kelas 4 SDN Karawang Wetan - Nidaa Lydia Mustika Nabiilah; Tubagus Tubagus; Dini Nurbaiti; Nur Aini Farida; M. Makbul (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This classroom action research aims to determine the increase in student learning motivation and also student learning outcomes by applying the Jigsaw cooperative learning model. The subjects of the panel were students of -. This research was conducted in 2 cycles, where one cycle consisted of two meetings. For data collection techniques using questionnaires to measure student learning motivation and test questions to measure student learning outcomes. The results of the study proved that the application of the Jigsaw learning model for 2 cycles has proven effective in increasing the learning motivation of grade 4 students of SDN Karawang Wetan 2. This can be seen from the increase in students' intrinsic and extrinsic motivation.